ANALYTICAL RADIAL PART SCHRODINGER EQUATION IN D-DIMENSIONS FOR ECKART PLUS MANNING ROSEN POTENTIAL AS THE QUANTUM PHYSICS LEARNING - Luqman Hakim; M. Nawir (BALANGA: Jurnal Pendidikan Teknologi dan Kejuruan, 2016)
The aims of the research are to determine energy spectra and radial wave function of Quantum system in D-Dimensions for Eckart plus Manning Rosen potential with Nikiforov-Uvarov method. NikiforovUvarov method is method for solving a second-order of differential equations by transforming the equation into the hypergeometric equation by the method of separation of intermediate variables by appropriate variable substitution. The analytical results is energy spectra and radial wave function visualization by Microsoft Excel 2010 and Mathematical Laboratory 2013 Programing. The visualization result can be showed that the orbital quantum number increase and the dimension increase causing the bounding energy decrease in the –n spectra energy. The probability visualization for ground state condition result can be showed that the orbital increase, so probability decrease, while the dimension increase for ground state condition is decreasing probability.